An anesthesiologist’s view of problems in HIV-positive patients (Perioperaciina Medicina, 2018)
Currently, HIV infection is becoming epidemic. More than 42% of HIV-infected people in the world are women of childbearing age. With the onset of antiretroviral therapy, chemoprophylaxis during pregnancy, and planned cesarean section, the risk of perinatal HIV transmission decreases to 1–2%. However, various side effects such as anemia, neutropenia, thrombocytopenia, fatty liver dystrophy, toxic hepatitis, acute pancreatitis, increased serum transaminases, changes in biochemical parameters of liver function, impaired glucose tolerance, and hypocoagulation may occur in the context of antiretroviral therapy. This poses to the anesthesiologist a number of new tasks to ensure patient safety during the perioperative period.
Keywords: HIV infection; perioperative period; treatment; patient; caesarean section